Isolation and Preliminary Characterization of L-Asparaginase-Producing Bacteria from Marine Sponges Collected in the Makassar Sea - Ayyub Harly Nurung; Siska Nuryanti; Iskandar Zulkarnain; Bintang Maharani; Fauzia Surman (Fakultas Farmasi Universitas Setia Budi, 2026)
This study provides an initial exploration aimed at discovering new sources of L-asparaginase from marine sponge-associated bacteria, representing a novelty due to the limited reports from the Makassar Sea ecosystem. The research addresses the need for alternative L-asparaginase producers with improved therapeutic potential and biological compatibility by isolating candidate bacteria from marine sponges. Isolation was performed using M9 and Asparagine Glucose Salt Agar to detect bacteria capable of hydrolyzing L-asparagine, indicated by the formation of pink halo zones. Three isolates (C6, B18, KH6) exhibiting the strongest responses were selected for further enzymatic evaluation using the Nessler method. The results revealed that isolate C6 displayed the highest activity (74.89 IU/mL), followed by B18 (58.44 IU/mL), whereas KH6 showed low activity (9.57 IU/mL). These findings demonstrate that marine sponges represent a promising reservoir of novel L-asparaginase-producing bacteria, with isolate C6 emerging as the most promising candidate for future purification and biochemical characterization. This study provides an important basis for developing alternative L-asparaginase sources for biotechnological applications.